Paulo Leminski, from São Paulo Concretism to the Post-Haiku - Cámara, Mario Cesar (2020)
In this essay, I examine part of the work of the Brazilian poet Paulo Leminski. From an analysis of his first poems, I define his differences from São Paulo?s concrete poets and demonstrate how Leminski developed a poetic project inspired by the genre of haikai. The "post-haiku" allowed Leminski to articulate a tradition of formal compositional rigor and the idea of poetry as experience.